ENCOURAGING BEHAVIOR SUPPORT TO CHANGE: THE ROLE OF INDIVIDUAL READINESS TO CHANGE AND COMMITMENT TO CHANGE - Dwi Indriastuti Yulianingsih; Olivia Fachrunnisa (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Every organization that wants to survive in today's competitive world must be aware of the external demands of the environment. Organizations are required to be able to respond the new challenges that will emerge such as globalization, the rapid flow o information and the fast of technological change, causes the need of qualified employees are increasing. This forces the organization to try to manage existing human resources to have adaptive and supportive behavior towards change. This study aims to examine the role of individuals’ readiness to change, change-oriented leadership, and commitment to change toward behavior support to change. Data were collected from 116 respondents and analyzed using Structural Equation Modeling (SEM) and Sobel Test. The results show that to encourage behavior that supports change, commitment to change is required as a result of individuals’ readiness to change and support from the leader especially leaders who have a change-oriented leadership. Keywords: change-oriented leadership; individual readiness to change; commitment to change; behavior support to change